Effects of varying midsole hardness on plantar pressure distribution and perception during basketball movements - Ng, Wei Xuan (2014)
Midsole alteration can improve footwear comfort, reduce plantar loading and stress injuries prevalent in basketball. Pressure distribution studies in basketball remain limited. This study investigates effects of midsole hardness on pressure distribution and perception during 4 basketball movements (Run, Sprint, 45° Cut, Lay-up). 20 experienced male basketball players participated in this within-subject study with 2 randomized experimental shoes (Soft Shoes (SS): 50c, Hard Shoes (HS): 60c). Participants performed 5 trials for each movement before switching shoes. Perceived shoe properties were assessed using Visual Analogue Scales after each movement. Entire process was then repeated with Pedar Mobile System (Novel, Germany) to obtain plantar pressure parameters. Combining shoes, significant main effect of movements in peak pressure (PP) and pressure time integral (PTI) across most plantar regions was observed (p < .05) with higher medial loading in other movements than running. Sagittal initial contact shoe-ground angle was similar between shoe conditions. SS elicited significantly lower total PP than HS in running (321.0 (49.0) kPa vs. 302.5 (40.0) kPa, p = .025) and sprinting (397.5 (75.6) kPa vs. 415.0 (65.1) kPa, p = .014), while only reducing stability in lay-up (16.6 (4.7) mm vs. 15.8 (4.6) mm, p = .025). No significant difference was found for total PTI between shoes for all movements. For perception, significant differences were present in “cushioning” and “overall comfort” between shoes in most movements (p < .05). SS was preferred to HS. Results provide pressure characteristics of basketball movements and revealed SS to be a potentially effective intervention to reduce plantar pressure, without compromising stability in most movements. Athletes’ perceived comfort and ability to discriminate between shoes is largely based on cushioning characteristics.